2006
DOI: 10.1002/bit.20891
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhibition treatment, type of inocula, and incubation temperature on batch H2 production from organic solid waste

Abstract: Two types of induction treatments (heat-shock pretreatment, HSP, and acetylene, Ac), inocula (meso and thermophilic) and incubation temperatures (37 and 55 degrees C) were tested according to a full factorial design 2(3) with the aim of assessing their effects on cumulative H(2) production (P(H), mmol H(2)/mini-reactor), initial H(2) production rate (R(i,H), micromol H(2)/(g VS(i) x h)), lag time (T(lag), h), and metabolites distribution when fermenting organic solid waste with an undefined anerobic consortia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 37 publications
0
26
1
1
Order By: Relevance
“…The largest average difference in lag time (~ 66 hours) was observed for S at thermophilic temperatures. Previous studies have also indicated that heat treatment can be detrimental to hydrogen production when compared to other methods (Cheong and Hansen, 2006;Valdez-Vazquez et al, 2006;Zhu and Béland, 2006). G and S also showed significant differences for the effects of temperature.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…The largest average difference in lag time (~ 66 hours) was observed for S at thermophilic temperatures. Previous studies have also indicated that heat treatment can be detrimental to hydrogen production when compared to other methods (Cheong and Hansen, 2006;Valdez-Vazquez et al, 2006;Zhu and Béland, 2006). G and S also showed significant differences for the effects of temperature.…”
Section: Resultsmentioning
confidence: 89%
“…Biohydrogen production from municipal solid waste has been well studied (Lay et al, 1999;Liu et al, 2006;Ueno et al, 2007;Valdez-Vazquez et al, 2005;Valdez-Vazquez et al, 2006). Even though municipal solid waste is comprised of 20-65% kitchen waste (Tchobanoglous et al, 1993), there have only been a few studies concerning hydrogen production from food waste.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations